Предмет: Алгебра,
автор: vahrushevamari
Доказать тождество
(cos^2x/1+sinx) - (sin^2x/1-cosx) = - sinx - cosx
Ответы
Автор ответа:
0
cos²x(1-sinx)/(1+sinx)(1-sinx)=cos²x(1-sinx)/(1-sin²x)=cos²x(1-sinx)/cos²x=1-sinx
sin²x(1+cosx)/(1-cosx)(1+cosx)=sin²x(1+cosx)/(1-cos²x)=sin²x(1+cosx)/sin²x=1+cosx
cos²x/(1+sinx)-sin²x/(1-cosx)=1-sinx-(1+cosx)=1-sinx-1-cosx=-sinx-cosx
sin²x(1+cosx)/(1-cosx)(1+cosx)=sin²x(1+cosx)/(1-cos²x)=sin²x(1+cosx)/sin²x=1+cosx
cos²x/(1+sinx)-sin²x/(1-cosx)=1-sinx-(1+cosx)=1-sinx-1-cosx=-sinx-cosx
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: Алгебра,
автор: evelinnik2006
Предмет: История,
автор: kosarevdanil47
Предмет: Русский язык,
автор: edita28
Предмет: Литература,
автор: надя2505
Предмет: Алгебра,
автор: karinalur